Pemberdayaan Masyarakat melalui Pelatihan Mitigasi dan Kesiapsiagaan Bencana di Nagari Pakan Sinayan - Rahmi Muthia; Fitri Mailani; Emil Huriani (Warta Pengabdian Andalas, 2020)
Disasters can come suddenly at anytime and anywhere. Disasters can result in many casualties, injuries, and material loss. Therefore, the community must understand the threat of a disaster, have knowledge about disaster preparedness. The purpose of this activity is to provide education and training on disaster management that may occur in the Pakan Sanayan village, Banuhampu District. The activity was held on August 8, 2020 in Nagari Pakan Sinayan, Banuhampu District, Agam Regency, and was attended by 47 community members. The activity begins with conducting a pretest to the training participants, providing material on potential disaster analysis followed by a discussion on disaster risk analysis that may occur in the Pakan Sinayan area. The material was continued with disaster mitigation and preparedness, especially disasters that could potentially occur in the area, namely landslides, earthquakes, fires and volcanic eruptions. The results of the evaluation showed an increase in public understanding and knowledge of disasters. It is recommended that this activity be carried out continuously to encourage community empowerment in improving disaster preparedness.